Responsible, competent and with a sense of belonging: an explanation for the purported levelling effect of CLIL. Issue 5 (28th May 2022) - Halbach, Ana; Iwaniec, Janina
ABSTRACT: Whilst CLIL research has flourished and showed some gains for CLIL learners, for example in motivation, there is little consensus about how it affects students from different social strata. The British Council 'English Impact' study (Shepherd and Ainsworth 2017, English Impact. An evaluation of English language capability . https://www.britishcouncil.es/sites/default/files/british-council-english-impact-report-madrid-web-opt.pdf ) has recently uncovered that CLIL contributes to the levelling of SES (socio-economic status) differences between students and leads to high levels of motivation in all students. In this study, we aim to follow up on these findings by exploring the factors that account for the curbed impact of SES in bilingual schools. To this end, 138 teachers from bilingual and non-bilingual schools filled in the TALIS questionnaire (OECD, 2013, Teaching and Learning International Survey (TALIS) 2013 Teacher Questionnaire. Retrieved from http://www.oecd.org/education/school/TALIS-2013-Teacher-questionnaire.pdf ) and 20 teachers were interviewed. Whereas questionnaire data reveals few perceived differences between students from the two types of schools, interviewees did point to differences in characteristics of students from bilingual and non-bilingual schools and the type of parental support they receive. The findings point towards the creation of a learning environment in CLIL programmes that satisfies the need for autonomy, competence and relatedness as reasons behind increased levels of motivation and the reduced impact of students' SES on their performance.